Effect Of Baby Massage On Gross Motor Development In Infants Aged 0-12 Months In Maharani Baby Care Girimarto Wonogiri - Kurniarum, Ari; Paryono, Paryono; Putri, Elizabeth Anindya (Poltekkes Kemenkes Palembang, 2022)
Background: Problem of developmental delays in Indonesia is still very much, even though the program to improve the quality of children is one of the government's priorities. About 30% of infants experience delays in gross motor skills. Lack of stimulation early in a child's life will stunt their emotional, social, physical and cognitive development. The problem that occurs today is that most mothers who have given birth do not massage their babies. The reason is because they don't know how to do baby massage, the benefits of baby massage and the fear of problems with the baby if the massage is wrong. Objective: This study aims to determine the effect of baby massage on gross motor development in infants aged 0-12 months at Maharani Baby Care, Girimarto Wonogiri. Methods: This research is a quantitative pre-experimental design study with a one group pretest-posttest design approach. The sampling technique used was probability sampling with a proportionate stratified random sampling technique with a sample of 53 infants. The research instrument used the DDST sheet. The data analysis technique used was Wilcoxon Signed Rank Test with significance level of 0.05 . Results: The results of statistical tests with the Wilcoxon Signed Rank Test, obtained a Z value of 5.196 with a probability value (p value) = 0.000, where p value (0.000) < 0.05, these results indicate that there is a significant effect between baby massage and gross motor development. for infants aged 0-12 months at Maharani Baby Care, Girimarto Wonogiri. Conclusion: There is an effect between baby massage and gross motor development in infants aged 0-12 months at Maharani Baby Care, Girimarto Wonogiri. Keywords : Baby massage, gross motor development, baby.